Pengaruh Program Pengembangan Kewirausahaan Terpadu (Jak Prenenur) Terhadap Omset Penjualan UMKM di Masa Pandemi Covid 19 di Wilayah Kecamatan Grogol Petamburan Jakarta Barat - Junaidi Hendro; Shabrina Arlinda (Jurnal Ekonomi, 2020)
The purpose of this research was to determine and analyze the influence of integrated entrepreneurship development program on UMKM sales omzet in the area Kecamatan Grogol Petamburan Jakarta Barat. The method used is quantitative method. The results showed that the increase in UMKM sales omzet that the entrepreneurship development program has an influence. Can be seen from result of regression variable of Entrepreneurship development program have value 0.111. Evident from the test with a tcount of 2.030 and ttable 2.000, with significance level 0.000 means less than the significance level 0.050. from this result then the testing criteria are tcount > ttable means Ha rejected and H0 accepted. Conclusion in this entrepreneur development program has a positive value and significance effect on UMKM sales omzet in the area Kecamatan Grogol Petamburan Jakarta Barat.